Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/1326861
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Aflatoxins in Date Palm (Phoenix dactylifera L.) Worldwide

Abstract: Due to global warming, the risk of aflatoxins exposure through the consumption of contaminated food has increased. Aflatoxins pose serious health hazards to humans’ and animals’ health because of their carcinogenic, mutagenic, and teratogenic properties and their immunosuppressive effects. Aflatoxin contamination in various agricultural commodities has attracted much attention worldwide. Date palm fruits are among these important commodities that are vulnerable to fungal contamination and consequent aflatoxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This is supported by a large screening study that compared the contamination levels of traded goods worldwide. Almaghrabi found that highly regulated markets, such as the European Union, have lower contamination levels compared to developing countries with less-well-regulated food systems [69].…”
Section: Toxins (Alkaloids and Mycotoxins)mentioning
confidence: 99%
“…This is supported by a large screening study that compared the contamination levels of traded goods worldwide. Almaghrabi found that highly regulated markets, such as the European Union, have lower contamination levels compared to developing countries with less-well-regulated food systems [69].…”
Section: Toxins (Alkaloids and Mycotoxins)mentioning
confidence: 99%
“…It completes its entire life cycle inside the trunk of date palm tree. About 300 eggs are deposited by the female in different holes or injured sections of the trunk [6][7][8]. The legless grubs hatch from these eggs after 2-5 days which readily start boring the interior of the trunk by feeding on the soft tissues and discarding the entire fibrous material.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several surveys conducted in the Mediterranean countries found that the aflatoxigenic aspergilli, particularly A. flavus and A. niger, are the more frequently detected mycotoxigenic fungi in dried dates, apricots, and prunes (Zohri and Abdel-Gawad, 1993;Aziz and Moussa, 2002;Heperkan, 2006). Moreover, A. flavus was also the main cause of aflatoxin contaminants in dried dates and prunes (Ozer et al, 2012) However, there is insufficient knowledge and a lack of published data regarding aflatoxin contamination of date palm fruits (Iqbal et al, 2014;Almaghrabi, 2022), Specifically, there is no published data reporting the occurrence of aflatoxin contamination in Ajwa dates. The studies of Al Hazzani et al (2014) and Al-Mutarrafi et al (2019) were designed to evaluate the fungal and bacterial loads in dried fruits (such as Sukkari, Mabroon, Amber, Ajwa, Rabeae, Mashrooq, Al Segae, Khodary, and Khalas), and the results confirmed Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%